2013
DOI: 10.4103/1817-1745.111425
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of giant terminal lipomyelocystocele with partial sacral agenesis

Abstract: Terminal myelocystoceles (TMCs) are a rare form of occult spinal dysraphism. They constitute approximately 5% of skin covered lumbosacral masses. The TMC is composed of a low-lying conus medullaris with cystic dilatation of caudal central canal, a surrounding meningocele and a lipoma that extends from the conus to a subcutaneous fat collection. A 6-month-old female child presented with a large lumbosacral mass (14 cm × 12 cm × 10 cm) and weakness at the ankle joints since birth. Magnetic resonance imaging and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The patient was paraplegic at time of presentation. Patients with giant TMC, as described in other case reports,[ 1 9 10 11 ] also had motor deficits in lower limb but none of them were paraplegic. Neurological deficits were reported in 47% patients by Gupta[ 12 ] in their series of 17 cases with TMC.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The patient was paraplegic at time of presentation. Patients with giant TMC, as described in other case reports,[ 1 9 10 11 ] also had motor deficits in lower limb but none of them were paraplegic. Neurological deficits were reported in 47% patients by Gupta[ 12 ] in their series of 17 cases with TMC.…”
Section: Discussionmentioning
confidence: 58%
“…Patients with giant TMC, as described in other case reports,[ 1 9 10 11 ] also had motor deficits in lower limb but none of them were paraplegic. Neurological deficits were reported in 47% patients by Gupta[ 12 ] in their series of 17 cases with TMC. Interestingly, Pang[ 5 ] in their study of 10 patients with TMC (four newborns and six older children) found that all the newborns were neurologically normal, whereas all the older children had neurological deficits.…”
Section: Discussionmentioning
confidence: 58%
“…"Giant" variant of TMC was not described by Pang et al [10] but reported by others. [2,3] Magnetic resonance imaging is characterized by a "trumpet like" flaring of the distal cord central canal into an ependymal lined terminal cyst. Abnormalities of the vertebral column may occur and include lordosis, scoliosis, and agenesis of the sacral parts.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Here, we present an interesting case of “giant” TMC, only rarely reported in the literature. [ 2 3 ]…”
Section: Introductionmentioning
confidence: 99%